Backstairs - Hardy, Jack (Grapevine Video, 2009)
Henny Porten's "Backstairs" (aka Hintertreppe) is one of the earliest attempts at reproducing a pioneering and revolutionary genre of German theatre called "intimate theatre" (Kammerspiel). This purposefully minimalistic film seized the imaginations of film critics, and helped pioneer a small but very influential subgenre of German film called the Kammerspielfilm; this film style would come to a greater fruition in F.W. Murnau's "Sunrise" (1927) and Hedy Lamarr's breakthrough film "Ecstasy" (1933), for example. Henny Porten's career correlates to that of America's Mary Pickford in many ways, except that Porten came off as a sexy mother figure, whereas Pickford was a sexy daughter figure. It should be of no surprise that Porten played many matronly characters in German movies, including an appearance as Mary, mother of Jesus, in the recently rediscovered 1924 German epic "I.N.R.I.". Most of Porten's films are difficult to find and few were released in America, so this is a rare opportunity to watch her in top form. [www.grapevinevideo.com]
Keywords: DVD-Video